Self-reported Metabolic Risk Factor Associations with Adenomatous, Sessile Serrated, and Synchronous Adenomatous and Sessile Serrated Polyps - Santiago, Celina N. (Cancer Prev Res (Phila), 2021)
Studies have found a positive association between metabolic risk factors, such as obesity and diabetes, and adenomatous polyps (APs). However, fewer studies have assessed the association between sessile serrated polyps (SSPs) or synchronous diagnosis of APs and SSPs (synch polyps). Study participants (N=1,370; ages 40–85) undergoing screening colonoscopy were enrolled between August 2016 and February 2020. Self-reported metabolic risk factors, including diabetes, hypertension, hyperlipidemia, and overweight/obesity, were evaluated for associations with new diagnoses of APs, SSPs, and synch polyps at the present colonoscopy. Average participant age was 60.73 ± 8.63 (SD) years; 56.7% were female and 90.9% white. In an assessment of individual metabolic risk factors adjusted for age, sex, race, and smoking status, increased BMI (overweight or obese vs normal BMI of <25 kg/m(2)) was associated with an increased odds for new onset of colon APs (p-value for trend, <0.001) as was a diagnosis of diabetes [aCOR=1.59 (1.10, 2.29)]. No associations were seen between the metabolic risk factors and onset of SSPs. Being obese or hypertensive each increased the odds of new onset of synch polyps with aCOR values of 2.09 (1.01, 4.32) and 1.79 (1.06, 3.02), respectively. Self-reported risk factors may help assess polyp type risk. Because SSPs and synch polyps are rare, larger studies are needed to improve our understanding of the contribution of these factors to polyp risk. These data lead us to hypothesize that differences in observed metabolic risk factors between polyp types reflect select metabolic impact on pathways to CRC.